C(sp3)−H Hydroxylation in Diiron β‐Hydroxylase CmlA Transpires by Amine‐Assisted O2 Activation Avoiding FeIV2O2 Species. (14th October 2022) - Lu, Jiarui; Lai, Wenzhen; Chen, Hui
Abstract: Through QM/MM modeling, we discovered that C(sp 3 )−H β ‐ hydroxylation in the diiron hydroxylase CmlA transpires by traceless amine‐assisted O2 activation. Different from the canonical diiron hydroxylase sMMO, this aliphatic‐amine‐assisted O2 activation avoids generating the high‐valent diferryl Fe IV 2 O2 species, but alternatively renders a diferric Fe III 2 O species as the reactive oxidant. From this unprecedented O2 activation mode, the derived C(sp 3 )−H hydroxylation mechanism in CmlA also differs drastically from the toluene aromatic C(sp 2 )−H hydroxylation in the diiron hydroxylase T4MO. This substrate‐modulated O2 activation in CmlA has rich mechanistic implications for other diiron hydroxylases with an amine group adjacent to the C−H bond under hydroxylation in substrates, such as hDOHH. Furthermore, the adapted coordination environment of the diiron cofactor upon O2 binding in CmlA opens up more structural and mechanistic possibilities for O2 activation in non‐heme diiron enzymes. Abstract : QM/MM modeling revealed that the C(sp 3 )−H β ‐ hydroxylation of L‐PAPA in the diiron hydroxylase CmlA transpires unprecedentedly through a traceless amine‐assisted O2 activation pathway. This novel O2 activation mode modulated by the L‐PAPA substrate, which is associated with the adapted coordination environment of the diiron cofactor upon O2 binding, opens up more structural and mechanistic possibilities in O2 activation by non‐heme diiron enzymes.